Kerangka Rekonstruksi Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Berbasis Teori Perkembangan Kognitif Piaget - Abdullah Hasan Busri; Adept Wahyu Wijaya; Azmi Izuddin; Achtim Wahyuni; Irfan Tamwifi (Edu Journal Innovation in Learning and Education, 2026)
Islamic Religious Education (PAI) in elementary schools faces a fundamental challenge: a gap between abstract instructional content such as monotheism (tawhid), eschatology, and worship obligations and students' cognitive capacity, which predominantly operates at the concrete operational stage (ages 7–11). This gap risks producing superficial understanding based solely on verbal memorization. This study aims to analyze the implications of Piaget's cognitive development theory in elementary PAI learning and to formulate appropriate instructional strategies. A Systematic Literature Review (SLR) following PRISMA standards was conducted on 10 articles selected from 150 identified sources. Findings reveal four effective strategies: experiential learning, the use of concrete and manipulative media, storytelling and role-playing methods, and structured cognitive conflict. This study produces a Piaget-Based PAI Learning Reconstruction Framework comprising five principles: phase-cognitive appropriateness, structured concretization, ZPD-based scaffolding, ongoing misconception evaluation, and meaningful reflection. This framework is intended as a practical guide for elementary PAI teachers in designing developmentally appropriate and meaningful learning experiences.